Dopamine D1 and Glutamate Receptors Co-operate With Brain-Derived Neurotrophic Factor (BDNF) and TrkB to Modulate ERK Signaling in Adult Striatal Slices - Morella, Ilaria; Hallum, Harriet; Brambilla, Riccardo (Frontiers in Cellular Neuroscience, 2020)
In the striatum, the input nucleus of the basal ganglia, the extracellular-signal-regulated kinase (ERK) pathway, necessary for various forms of behavioural plasticity, is triggered by the combined engagement of dopamine D1 and ionotropic glutamate receptors. In this study, we investigated the potential crosstalk between glutamatergic, dopaminergic and Brain derived Neurotrophic Factor (BDNF)-TrkB inputs to ERK cascade by using an ex-vivo model of mouse striatal slices. Our results confirmed that the concomitant stimulation of D1 and glutamate receptors is necessary to activate ERK in striatal medium spiny neurons (MSNs). Moreover, we found that ERK activation is significantly enhanced when BDNF is co-applied either with glutamate or the D1 agonist SKF38393, supporting the idea of a possible integration between BDNF, glutamate, and D1R-mediated signalling. Interestingly, ERK activation via BDNF-TrkB is upregulated upon blockade of either AMPAR/NMDAR or D1 receptors, suggesting a negative regulatory action of these two neurotransmitter systems on BDNF-mediated signalling. Conversely, the TrkB antagonist cyclotraxin B partially prevents glutamate- and D1-mediated ERK activation. Altogether, these results suggest a complex and unexpected interaction among dopaminergic, glutamatergic and BDNF receptor systems to modulate the ERK pathway in striatal neurons.